Effectiveness of Antioxidants on Cell Viability in Beta-amyloid Exposed PC12 Cells. (7th June 2021) - Rotvold, Annika; Parker, Kelly; Rhee, Yeong
Abstract: Objectives: Beta-amyloid (BA) is toxic to cells, and leads to cell damage, decreasing cell viability. Certain antioxidants, however, have been shown to prevent BA induced cell damages. The purpose of this research was to determine whether antioxidants affect the viability of PC12 cells that have been exposed to BA. Methods: PC12 cells (2 × 10 5 cells/ml) were treated with secoisolariciresinol diglucoside (SDG) at either a concentration of 50 μM or 100 μM, superoxide dismutase (SOD) at a concentration of 100 U/ml, catalase (CAT) at a concentration of 100 U/ml, or a combination of both SOD and CAT for two hours. Following the antioxidant treatment, cells were treated with BA at a concentration of 10 μM for 24 hours. Once the cell treatments were completed, cell viability was measured using an MTT assay. Student's t-test was performed to determine significance ( P < 0.05) between the treated cells and the control cells (no antioxidant or BA treatment). Results: The results showed that there were no significant changes in cell viability in antioxidant treated cells that were exposed to BA compared to the control cells. The only cells that showed a significant change in cell viability compared to the control were the cells treated with SOD + CAT and no BA. Conclusions: PC12 cells treated with antioxidants remained just as viable after being exposed to BA as control cells that were not treated with antioxidants or exposed to BA. These results indicate that SDG, an antioxidant found in flaxseed, as well as SOD and CAT, may be an effective method in the prevention of damage caused by BA in PC12 cells. Funding Sources: This research was funded by the College of Human Sciences and Education at North Dakota State University.